Sistematika Pemilihan DPD Dalam Penguatan Otonomi Daerah Melalui Pemilihan Umum - Anhar Nurdiansyah Harahap (Pusat Riset dan Inovasi Nasional, 2024)
The general election is one way for people to choose the candidates they want, including the DPD election, so that the rights of the people can be represented. In the Daerah Perwakilan Dewan. The purpose of this DPD election will be to determine how autonomous the various areas will be in the future. In order to generate candidate leaders who can help strengthen the autonomy of the region and so improve the well-being of the people themselves, the study's objective is to describe and analyze the systematics of the election of DPD members through general elections in the region. The researchers also sought to clarify the connection between the DPD's function and mission, as well as its authority in its positions within government, and regional autonomy. The research conducted for this study is of the qualitative variety. It is completed using a library study methodology based on phenomena that seek to concentrate research from prior scientific works as research material or data sources. According to the research's findings, the DPD plays a role in enhancing the region's autonomy so that the elections can be held in a transparent manner. According to the statute currently in effect, there are numerous steps necessary to elect the DPD, and these steps range from preparation through the appointment of a candidate member. Everything in the Indonesian elections is strictly regulated by BAWASLU, often to the point of infractions. This study's conclusion is that Indonesia's elections to date have been quite successful because they feature a number of stages that allow for a well-organized selecting process. Up until the appointment of all candidates is organized, the systematic general election of the DPD starts with the preparation of the minimal submission of support.